Perilaku Merokok Orangtua dengan Kejadian ISPA Pneumonia Pada Balita - Anika Ardila; Noraida Noraida; Erminawati Erminawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
Abstract: The Parental Smoking Behavior With The Occurrence Of Pneumonia Disease. Pneumonia is an acute infection process that affects the lung tissue (alveoli), with symptoms of rapid breathing and shortness of breath due to sudden lung inflammation. Pneumonia is caused by bacteria, Streptococcus pneumonia (peumokokus).The purpose of this study to determine the correlation between smoking behavior with the occurrence of pneumonia disease over toddlers in the region Public Health Center of Sungai Ulin Banjarbaru in 2018. The type of this research was analytical research with retrospective approach with 1: 2 sample ratio. The case population was all families who have toddler with pneumonia diseases with case sampling 31 toddler and control population were all families with toddler not pneumonia with sampling 62 Toddler. The results showed the parental smoking behavior of 63 (65.6%) respondents and pneumonia disease of 31 (32.2%) cases. There was correlation of parental smoking behavior with the occurrence of pneumonia disease in infants with p value = 0.018